Aplicações e desafios em biomateriais poliméricos para fabricação de corações artificiais e dispositivos cardiovasculares - Rodrigues, Lucas Guerra Caires (Universidade Federal de São Carlos, 2025)
This study aims to present an in-depth review of the main polymers used in implantable cardiovascular devices, discussing their structural properties, chemical stability, biological response, and future perspectives regarding their clinical application. Relevant cases of synthetic heart valves and artificial hearts based on advanced materials, such as polycarbonate urethane (PCU), POSS-PCU, SiPUU, and FGO-PCU, are analyzed. These polymers have demonstrated excellent fatigue resistance, flexibility, and low susceptibility to calcification, making them highly suitable for environments subject to intense cyclic loading, such as the intracardiac system. In addition to the material characterization, the study emphasizes the influence of manufacturing techniques, including electrospinning, solution casting, and 3D printing, on the definition of morphology, fiber orientation, and functional performance of the devices. In the context of artificial hearts, case studies such as the SynCardia Total Artificial Heart (TAH) and the experimental Soft Total Artificial Heart (sTAH) highlight the importance of geometric customization, biomimetic design, and careful selection of elastomeric materials, such as PDMS and reinforced silicone composites, to ensure effective hemodynamic performance and structural durability. Finally, emerging trends in the use of polymeric biomaterials are discussed, including the development of smart polymers capable of responding to physiological stimuli, systems with controlled degradation, biofunctionalized surfaces, and devices tailored through advanced additive manufacturing techniques. These advances aim to enhance the functionality, safety, and longevity of implantable devices, contributing to broader access to innovative therapies and reducing dependence on heart transplants.
Applications and challenges in polymeric biomaterials for the manufacture of artificial hearts and cardiovascular devices
Keywords: Biomateriais; Polímeros; Válvulas cardíacas; Coração artificial; Engenharia de tecidos; Biomaterials; Polymers; Heart valves; Artificial heart; Tissue engineering; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS